1989
DOI: 10.1007/bf01953048
|View full text |Cite
|
Sign up to set email alerts
|

The pineal and melatonin: Regulators of circadian function in lower vertebrates

Abstract: Summary. The pineal has been identified as a major circadian pacemaker within the circadian system of a number of lower vertebrates although other pacemaking sites have been implicated as well. The rhythmic synthesis and secretion of the pineal hormone, melatonin, is suggested as the mechanism by which the pineal controls circadian oscillators located elsewhere. Both light and temperature cycles can entrain the pineal melatonin rhythm. The pineal, therefore, acts as a photo and thermoendocrine transducer which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
5

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 47 publications
(5 reference statements)
2
46
0
5
Order By: Relevance
“…Lantern sharks like other deep-sea shark species possess a 'pineal window' and it has already been suggested that visual information collected by the pineal gland help these fishes to accomplish their vertical migrations (Clark and Kristof, 1990). Assuming that the visual information from the pineal gland is mediated by a release of MT in the blood (Underwood, 1989;Arendt, 1997) and because MT triggers light emission in a dose-dependent manner in E. spinax, this hormone could make a direct connection between ambient light and luminescence intensity in this shark. This could allow E. spinax to match the intensity of downwelling light with its luminescence, which is particularly convenient for camouflage by counter-illumination, a function already suggested for this shark's luminescence (Claes and Mallefet, 2008;Claes and Mallefet, 2009).…”
Section: Comparative Control Of Luminescence In Fishesmentioning
confidence: 99%
“…Lantern sharks like other deep-sea shark species possess a 'pineal window' and it has already been suggested that visual information collected by the pineal gland help these fishes to accomplish their vertical migrations (Clark and Kristof, 1990). Assuming that the visual information from the pineal gland is mediated by a release of MT in the blood (Underwood, 1989;Arendt, 1997) and because MT triggers light emission in a dose-dependent manner in E. spinax, this hormone could make a direct connection between ambient light and luminescence intensity in this shark. This could allow E. spinax to match the intensity of downwelling light with its luminescence, which is particularly convenient for camouflage by counter-illumination, a function already suggested for this shark's luminescence (Claes and Mallefet, 2008;Claes and Mallefet, 2009).…”
Section: Comparative Control Of Luminescence In Fishesmentioning
confidence: 99%
“…A primary role for circulating melatonin in regulating various seasonal changes in physiology, such as reproduction, metabolism and hair growth, in many photoperiodic species is well-established (Tamarkin et al, 1985; Bartness & Goldman, 1989). Pineal melatonin is also involved in regulating circadian rhythms in some species of birds and reptiles (Underwood, 1989) and, low doses of exogenous melatonin entrain free-running rhythms in mammals (Redman et al, 1983;Folkard et al, 1990;Thorpe & Coen, 1994), while larger doses of have a sleep-promoting and sedative effect in both experimental animals and man (Holmes & Sugden, 1982;Waldhauser et al, 1990). Small amounts of melatonin are also synthesized by the photoreceptors of some species where it probably acts locally to regulate various aspects of retinal physiology such as photoreceptor retinomotor movements and photoreceptor outer segment disc shedding (Besharse et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is synthesized in the pineal gland of all vertebrates; circulating melatonin exhibits a daily rhythm, with markedly elevated levels occurring at night (1)(2)(3), hence the moniker "hormone of the night." Circulating melatonin regulates seasonal changes in various aspects of physiology in photoperiodic species (4,5) and has been implicated in the mechanisms that regulate circadian rhythms in some species of birds, reptiles, and mammals (2,3,6,7). A second site of melatonin synthesis is the retina, where it probably acts locally as a paracrine signal to regulate various aspects of retinal physiology (8,9).…”
mentioning
confidence: 99%